A 16-year-old girl with anti-NMDA-receptor encephalitis and family history of psychotic disorders. Issue 6 (1st June 2015) - Cleland, Neil; Lieblich, Samuel; Schalling, Martin; Rahm, Christoffer
Abstract : Background: Autoimmune NMDA-R encephalitis (ANRE) shares clinical features with schizophrenia. Recent research also indicates that both disorders are associated with dysfunction of the N -Methyl-D-Aspartate glutamate receptors (NMDA-R) subunit 1. Methods: We present the case of Ms A, 16 years old. Ms A presented with acute personality change, bizarre behaviour, delusional ideas and atypical seizures. She had a family history of psychotic disorders, and autistic traits diagnosed in childhood. She was initially diagnosed with a psychotic disorder. Delayed testing of CSF indicated ANRE. As the patient was a Jehovah's witness the treating team was unable to use gammaglobulin therapy; they instead relied on combined plasmapheresis and rituximab. To exclude the possibility that the affected members of this family shared a gene coding for an abnormal configuration of the NMDA receptor subunit 1 we sequenced the region of the GRIN1 gene in DNA extracted from blood in both Ms A and her grandmother. Results: Ms A's condition improved dramatically, though her long-term memory is still demonstrably impaired. No genetic abnormality was detected. Conclusions: This case emphasizes how important it is, for a first episode psychosis, to exclude ANRE and other autoimmune synaptic encephalitides, even in the face of significant family history, and if seronegative, the importance of testing for CSF autoantibodies.